Combining models to generate a consensus effective reproduction number R for the COVID-19 epidemic status in England - Manley, H; Park, J; Bevan, L; Sanchez-Marroquin, A; Danelian, G; Bayley, T; Bowman, V; Maishman, T; Finnie, T; Charlett, A; Watkins, NA; Hutchinson, J; et al. (Cambridge University Press, 2024)
The effective reproduction number R was widely accepted as a key indicator during the early stages of the COVID-19 pandemic. In the UK, the R value published on the UK Government Dashboard has been generated as a combined value from an ensemble of epidemiological models via a collaborative initiative between academia and government. In this paper, we outline this collaborative modelling approach and illustrate how, by using an established combination method, a combined R estimate can be generated from an ensemble of epidemiological models. We analyse the R values calculated for the period between April 2021 and December 2021, to show that this R is robust to different model weighting methods and ensemble sizes and that using heterogeneous data sources for validation increases its robustness and reduces the biases and limitations associated with a single source of data. We discuss how R can be generated from different data sources and show that it is a good summary indicator of the current dynamics in an epidemic.